APLIKASI DOA SEHARI HARI UNTUK UMAT MUSLIM BERBASIS ANDROID STUDIO - Randi Andika; Muhammad Ihsan (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
In the context of Islam, prayer plays a central role in the daily lives of Muslims. Prayer serves not only as a means to seek protection or request needs but also as a form of worship and direct communication with Allah. This study develops an application called "Daily Prayers for Muslims" based on Android Studio, designed to bridge the needs of modern Muslims with the convenience of technology. This application provides quick and practical access to various prayers, worship guidelines, and other religious information. System testing was conducted thoroughly using the waterfall method, ranging from planning, analysis, design, implementation, to maintenance. The testing results indicate that this application functions well and meets user needs. This research concludes that this daily prayer application can be a practical solution for Muslims in the digital era to remain connected with their spirituality. Thus, the application not only enhances the accessibility of prayers but also strengthens individuals' spiritual relationships with Allah, providing a more integrated and meaningful worship experience. Through the development of information technology, it is hoped that Muslims can more easily carry out their worship and obtain relevant information related to their religious teachings.